(untitled) (Psychology Travelogs, 2025)
The article theoretically substantiates the role of art work with clay in improving the communication skills of older preschool children. The concepts of «skills», «communication» are considered and the understanding of the concept of «communicative skills» is presented. The features of the formation of communicative skills in children of senior preschool age are described. The concepts of «sculpting», «visual activity», as well as the features of clay as a material for creativity are considered. It is shown that clay is a universal material that is effective for creative work with children of senior preschool age. Working with clay relieves mental tension, which often interferes with communication, in particular when establishing interpersonal contact; promotes self-disclosure by the child, the child’s knowledge of himself and peers; gives an occasion for communication; helps to gain recognition from adults, which adds confidence and desire for further communication with others. Creative work with clay opens up great opportunities for solving specific tasks, among which we can highlight: the development of fine and gross motor skills; sensory stimulation; the formation of visual-spatial representations; the development of creative abilities; emotional response; making clay products contributes to: the development of intelligence; motivation for active participation in the socio-cultural space; increasing self-esteem; mastering communication skills. In the context of the development of communication skills of older preschool children, clay is helpful due to the relief of mental tension, which is often an obstacle to the child’s self-expression in communication, creating an atmosphere of play and creativity that is as natural as possible for the child Prospects for further research consist in conducting an empirical study on the influence of creative work with clay on the improvement of communication skills in older preschool children.